Effectiveness of Interpersonal Communication between Teachers and Students in the Learning System - Rosalina Valencia Sapphine; Sinta Paramita (Syntax Corporation Indonesia, 2024)
The key to successful education as a process or learning activity lies in the teacher's competencies to build effective communication with students in their learning process. This study uses a case study method at Wardaya College and measures the effectiveness of interpersonal communication in the learning system based on various indicators (openness, empathy, supportiveness, positiveness and equality). The sample consisted of 5 teachers out of 26 teachers and 11 students out of 85 students. The results of the study show a gap between the opinions of teachers and students. Teachers believe they have engaged in interpersonal communication, provided methods that are easy for students to understand, demonstrated empathy, consistently offered motivational support, maintained a positive attitude, and positioned students themselves as equals during teaching and learning activities. However, this is not consistent with the opinions of some students. Some students stated that it was not easy to understand the communication from some teachers, not all teachers showed openness in interactions, empathy, or presented content in ways that captured students' attention, nor did they give recognition or appreciation for students' efforts, and displayed a positive attitude and equality. This gap indicates areas for improvement within the institution.